"Historia Armenii" Agathangelosa jako źródło do poznania chrześcijańskich dziejów Armenii - Próchniak, Daniel (Vox Patrum, 1983)
The principal source to the earliest period of Christian Armenia is the "History" of Agathangelos. His work survives in four versions written in four different languages.